EGFR amplification is a putative resistance mechanism for NSCLC–LM patients with TKI therapy and is associated with poor outcome - Yang, Hainan; Wen, Lei; Zhao, Chao; Li, Xuefei; Shan, Changguo; Liu, Da; Hong, Weiping; Zhou, Zhaoming; Zhou, Cheng; Cai, Linbo; Zhou, Caicun (Frontiers in Oncology, 2022)
Background Leptomeningeal metastases (LM) have become increasingly common in NSCLC patients who harbor epidermal growth factor receptor (EGFR) mutation treated with EGFR-TKI and are correlated with inferior prognosis. Evidence in prior research demonstrated that EGFR amplification was more likely presented in advanced clinical stages and was associated with worse survival. However, whether the EGFR amplification is a prognostic marker in NSCLC-LM is still inconclusive. Methods This study enrolled patients diagnosed with NSCLC-LM from June 2019 to September 2021, who had received previous EGFR-TKI at Guangdong Sanjiu Brain Hospital. Cerebrospinal fluid (CSF) samples were collected and subjected to targeted next-generation sequencing (NGS) of 168 cancer-related genes. Clinical characteristics and overall survival (OS) were compared in patients with and without EGFR amplification. Results This study enrolled 53 NSCLC-LM patients, all of whom had EGFR mutations. TP53 and EGFR amplification are the two most frequent mutations in the study cohort, presenting 72% (38 of 53) and 40% (21 of 53), respectively. The rate of EGFR amplification was much higher at the time of leptomeningeal progression than at initial diagnosis (p<0.01). Karnoskfy performance status was poorer (p=0.021), and CSF pressure was higher (p=0.0067) in patients with than without EGFR amplification. A multivariable Cox proportional hazard regression model showed that EGFR amplification was an independent prognostic factor for poorer OS (8.3 vs 15 months; p=0.017). Median OS was shorter in NSCLC-LM patients with mutated than wild-type TP53, but the differences was not statistically significant (10 vs 17.3 months, p=0.184). Conclusions EGFR gene amplification could be a potential resistance mechanism to EGFR-TKI failure in NSCLC-LM and is associated with inferior clinical outcomes.